2013
DOI: 10.1039/c3an36782g
|View full text |Cite
|
Sign up to set email alerts
|

A new method to measure oxygen solubility in organic solvents through optical oxygen sensing

Abstract: A new method to measure oxygen concentration in air-saturated organic solvents and binary mixtures has been developed. The methodology relies on the ability of HPLC columns to retain the molecular oxygen contained in different types of solvents which are injected into the system at 298.15 K. The outlet of the HPLC is coupled with an optical oxygen sensor which continuously measures changes in oxygen partial pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
81
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 16 publications
7
81
0
Order By: Relevance
“…As a follow-up to these early findings, our most recent investigations have now brought to light the great reactivity of this class of compounds towards dioxygen. When irradiated in air-saturated CH 3 CN solution, 46 we have observed that the colorless endoperoxide 2-O 2 , formally obtained by cycloaddition of one O 2 entity onto the open isomer 2 (Scheme 1), can be produced quantitatively at room temperature and that the back reaction is also complete. Compounds 2 and 2-O 2 can thus be produced quantitatively by direct irradiation at λ ≥ 630 nm of a solution of 1 in the absence or presence of air respectively.…”
mentioning
confidence: 98%
“…As a follow-up to these early findings, our most recent investigations have now brought to light the great reactivity of this class of compounds towards dioxygen. When irradiated in air-saturated CH 3 CN solution, 46 we have observed that the colorless endoperoxide 2-O 2 , formally obtained by cycloaddition of one O 2 entity onto the open isomer 2 (Scheme 1), can be produced quantitatively at room temperature and that the back reaction is also complete. Compounds 2 and 2-O 2 can thus be produced quantitatively by direct irradiation at λ ≥ 630 nm of a solution of 1 in the absence or presence of air respectively.…”
mentioning
confidence: 98%
“…Indeed, unlike other plasmonic nanomaterials such as gold or silver, copper SPR is commonly reported to red shift when the size of the NPs is smaller. [1] Three main parameters may influence the oxidation rate of the particles: their size, the diffusion rate of dioxygen inside the solvent, [25] and the interaction of the ligand with the surface of the nanoparticles.…”
Section: Oxidation Of the Particlesmentioning
confidence: 99%
“…[49] Sulfoxidationk inetics ([(L 2 )Fe IV =O] 2 + ,t hioanisole, MeCN, 298.15 K) [50] have been run under pseudo-first order conditions, resultingi ns econd-order rate constantso f( 4.80 AE 0.02) 10 2 m À1 s À1 and (1.17 AE 0.03) m À1 s À1 for the first and second sulfoxidations tep. This is in agreement with the time-dependent measurement of O 2 in the aqueous solutions and the headspace under standard reaction conditions: [7] the concentration of O 2 decreases in the aqueous phase from saturation (260 mm at ambient temperature [51][52][53] )t oo xygenfree within approximately 5sec. This is in agreement with the time-dependent measurement of O 2 in the aqueous solutions and the headspace under standard reaction conditions: [7] the concentration of O 2 decreases in the aqueous phase from saturation (260 mm at ambient temperature [51][52][53] )t oo xygenfree within approximately 5sec.…”
Section: Introductionmentioning
confidence: 99%